Characterization of a mouse-adapted strain of bat severe acute respiratory syndrome-related coronavirus - Lin, Hao-Feng; Liu, Mei-Qin; Jiang, Ren-Di; Gong, Qian-Chun; Su, Jia; Guo, Zi-Shuo; Chen, Ying; Jia, Jing-Kun; Dong, Tian-Yi; Zhu, Yan; Li, Ang; Shen, Xu-Rui; et al. (Journal of virology, 2023)
Bats carry genetically diverse severe acute respiratory syndrome-related coronaviruses (SARSr-CoVs). Some of them utilize human angiotensin-converting enzyme 2 (hACE2) as a receptor and cannot efficiently replicate in wild-type mice. Our previous study demonstrated that the bat SARSr-CoV rRsSHC014S induces respiratory infection and lung damage in hACE2 transgenic mice but not wild-type mice. In this study, we generated a mouse-adapted strain of rRsSHC014S, which we named SMA1901, by serial passaging of wild-type virus in BALB/c mice. SMA1901 showed increased infectivity in mouse lungs and induced interstitial lung pneumonia in both young and aged mice after intranasal inoculation. Genome sequencing revealed mutations in not only the spike protein but the whole genome, which may be responsible for the enhanced pathogenicity of SMA1901 in wild-type BALB/c mice. SMA1901 induced age-related mortality similar to that observed in SARS and COVID-19. Drug testing using antibodies and antiviral molecules indicated that this mouse-adapted virus strain can be used to test prophylactic and therapeutic drug candidates against SARSr-CoVs.